A Priori Error Estimates for Obstacle Optimal Control Problem, Where the Obstacle Is the Control Itself (Journal of Computational Mathematics, 2023)
In this paper we deal with the convergence analysis of the finite element method for an elliptic penalized unilateral obstacle optimal control problem where the control and the obstacle coincide. Error estimates are established for both state and control variables. We apply a fixed point type iteration method to solve the discretized problem.To corroborate our error estimations and the efficiency of our algorithms, the convergence results and numerical experiments are illustrated by concrete examples.